Assessing needs for developing a multisensory room design with Javanese gestures for older adults - Mendrofa, Fery Agusman Motuho; Hani, Umi; Widyastuti, Rita Hadi; Murniati, Restu; Pratama, Wisnu (Public Health of Indonesia, 2023)
Background: Multisensory stimulation in the elderly helps train cognitive function and motor skills by incorporating elements that stimulate their senses. The application of a multisensory room caters to sensory stimulation identified for individuals experiencing cognitive decline from moderate to severe and those with neurodegenerative conditions such as Parkinson's, Dementia, and Alzheimer's. Objective: This study aimed to assess needs to develop a multisensory room design tailored with a Javanese cultural approach for the older adults. Methods: A plan for a multisensory room was made involving experts in gerontic nursing, design, and interior space design. Qualitative data collection utilized the Focus Group Discussion (FGD) technique. FGD was employed to comprehend factors associated with the necessity of a therapeutic room for the elderly, especially concerning the functionality of the multisensory space. Additionally, the FGD sought to identify Javanese cultural elements applicable to the room concept. Participants in the FGD included geriatric nurses, representatives from Alzheimer's Indonesia, Javanese cultural experts, architects, and Health Service members. The analysis of FGD results was conducted using the Colaizzi method. This involved creating transcripts from the FGD, multiple readings of the transcripts, extracting significant statements, validation with participants, and formulating meaningful themes, sub-themes, and categories. The themes identified during the data analysis were integrated and presented as research outcomes. Results: Two themes emerged from the analysis: aspects that need to be considered when creating a multisensory room and the elements in a multisensory room. Conclusion: By addressing the demand for innovative elderly health services and collaborating with stakeholders in developing spatial models, this study anticipates the creation of applicable and beneficial space designs. This endeavor aims to validate the effectiveness of the applied concepts in line with evolving health needs, particularly concerning the elderly population.